Case report: Experience of a rare case of rebound of the Kasabach-Merritt phenomenon during sirolimus treatment in kaposiform hemangioendothelioma - Wang, Liang; Li, Jing; Wu, Changhua; Song, Dan; Liu, Zhuang; Niu, Yanli; Zhou, Jie; Guo, Lei (Frontiers in Pediatrics, 2022)
Kaposiform hemangioendothelioma (KHE) is a rare vascular neoplasm associated with the Kasabach–Merritt phenomenon (KMP), which is a consumptive coagulopathy with associated potentially life-threatening thrombocytopenia. There are no standardized treatment protocols for the management of KHE with KMP. Moreover, there are limited reports regarding the treatment of cases of rebound. Herein, we describe a rare case of rebound of KHE/KMP, during systemic sirolimus treatment, successfully treated with embolization and vincristine infusion combined with microwave ablation.